2020
DOI: 10.4103/lungindia.lungindia_52_20
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucinous carcinomas of the lung: Clinical characteristics and treatment outcomes

Abstract: Introduction: Invasive mucinous adenocarcinoma (IMA) of the lung is a distinct histologic variant of adenocarcinomas comprising about 2%–10% of lung adenocarcinomas. A large proportion of IMAs carry KRAS mutations and only rarely epidermal growth factor receptor (EGFR) mutations or ALK/ROS translocations; thus, most cases are not amenable for targeted therapy at present. This study was conducted to elicit the unique clinicopathological characteristics of IMA. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Because of limited reported cases, there was no significant clinicopathologic prognosticator for pneumonic-type IMA, even the recognized TNM staging. For the relationship between pneumonic-type IMA and bad prognosis, a possible explanation is that the tumor mimic pneumonia on imaging, thus delaying diagnosis and treatment [ 28 , 29 ], but it still doesn't explain those patients still had a shorter survival time who accepted an undelayed operation. Systematic inflammatory response is a common accompaniment to pneumonic-type IMA, may lead to an elevated SII.…”
Section: Discussionmentioning
confidence: 99%
“…Because of limited reported cases, there was no significant clinicopathologic prognosticator for pneumonic-type IMA, even the recognized TNM staging. For the relationship between pneumonic-type IMA and bad prognosis, a possible explanation is that the tumor mimic pneumonia on imaging, thus delaying diagnosis and treatment [ 28 , 29 ], but it still doesn't explain those patients still had a shorter survival time who accepted an undelayed operation. Systematic inflammatory response is a common accompaniment to pneumonic-type IMA, may lead to an elevated SII.…”
Section: Discussionmentioning
confidence: 99%
“…It was formerly known as bronchioloalveolar cell carcinoma [ 3 ]. It accounts for about 5% of lung carcinomas [ 4 ]. The diagnosis can be difficult on small biopsy specimens [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for about 5% of lung carcinomas [ 4 ]. The diagnosis can be difficult on small biopsy specimens [ 4 ]. This type of tumor does not have a specific clinical manifestation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two other studies revealed that resectable and stage IV IMAs exhibited better OS than non-IMAs with similar characteristics [ 53 , 54 ]. These inconsistent results may be attributed to prognostic differences among IMA phenotypes or the presence of prognosis-related factors such as spread through air spaces (STAS) or mucin-producing characteristics [ 44 , [55] , [56] , [57] , [58] ]. Additional research on histology-related prognosis or prognosis-related factors could help identify more suitable candidates for lung transplantation and broaden the indications for this procedure.…”
Section: Indications For Lung Transplantationmentioning
confidence: 99%